"Intolerance of uncertainty" mediates the relationship between social profile and anxiety in both Williams syndrome and autism. Issue 9 (10th June 2021) - South, Mikle; Hanley, Mary; Normansell‐Mossa, Karys; Russell, Nicholas C. C.; Cawthorne, Thomas; Riby, Deborah M.
Abstract: Anxiety is the most significant mental health concern for both Williams syndrome (WS) and autism. Whilst WS and autism are characterized by some syndrome‐specific social differences, less is known about cross‐syndrome profiles of anxiety symptoms. Previous research has shown that Intolerance of Uncertainty (IU) is a core mechanism of anxiety maintenance for clinically anxious populations and for autistic children, adolescents, and adults. The only published study in this area for WS has shown some similar patterns—with an added emphasis on the role of sensory sensitivities—in a sample of older teens and adults (mean age = 24), with the authors highlighting the need for younger samples to consider developmental influences. Here we report a cross‐syndrome, cross‐sectional mediation analyses of children diagnosed with WS or autism, including data from parent surveys of 90 children with WS ( n = 48) or autism ( n = 42). Group differences showed higher trait levels on all measures for the autism group. Importantly, the relationship between social profile and anxiety was fully mediated by IU level for both groups. This suggests possible similar core mechanisms underlying anxiety in these conditions, and the possibility of generalized intervention approaches especially related to managing distress related to uncertainty in multiple contexts. Lay Summary: Autism and Williams Syndrome share some similarities in social profile and also in anxiety traits, but there are also some key differences as well. Comparing them side‐by‐side at the same time improved identification of ways to reduce feelings of anxiety. We found that the intolerance of uncertainty affected the relationship between social profile and anxiety in the same way for young children diagnosed with autism or Williams syndrome, meaning that intervention approaches could be similar for both.